Effect of Molecular Mutagenesis on Alcohol Dehydrogenase Production by Pseudomonas fluorescens RB30 - Hadi, Noora A; Al-Gelawi, Majed H; Aziz, Ghazi M (Al-Nahrain Journal of Science, 2013)
Alcohol dehydrogenases are group of dehydrogenase enzymes that occur in many organisms and facilitate the interconversion between alcohols and aldehydes or ketons with the reduction of NAD+ to NADH. Locally isolated Pseudomonas fluorescens RB30 was selected depending on its efficiency in producing of alcohol dehydrogenase (ADH) enzyme. Its specific activity was 13.6 U/mg proteins after extraction by using lysozyme. As an attempt to improve ADH production, Pseudomonas fluorescens RB30 was subjected to molecular mutagenesis following conjugation with E. coli PULB113, Tetr and Kmr harboring the conjugative plasmid RP4 that carried Mini-Mu transposon, and two mutants were due to their high activities were resulted (0.82 U/ml and 0.79 U/ml respectively). Alcohol dehydrogenases